Optimizing Edible Sorghum Bowls: Effects of Roasting and Edible Flower Powder Enhancement on Technological, Nutritional, Antioxidant, and Functional Properties - Devatha Manivel; Raajeswari Paramasivam; Swarup Roy (International Journal of Food Science)
The widespread reliance on single-use plastics (SUPs) has fostered a global throwaway culture, especially in the food packaging industry, where convenience and low cost have driven their adoption, posing serious environmental threats, particularly to marine ecosystems and biodiversity. Edible and ecofriendly packaging made from millet, specifically sorghum (Sorghum bicolor (L.) Moench), is a promising solution to mitigate SUP consumption and promote sustainability. This study explores the development of edible sorghum bowls, enhanced through roasting and incorporating 3 g of hibiscus and rose flower powders. The standardized sorghum bowl was analyzed for nutritional value; optical, technological, functional, and mechanical properties; and shelf life, and the results were discussed. The bowls, 18.5 g of average weight, dimensions of 10.2 cm, and a thickness of 3 mm, were baked in a unique bowl-shaped mold at 80°C for 7 min. Enhancing the bowls with flower powder improved their optical properties and nutrient content. The addition of flower powder also increased phytochemical levels, according to qualitative analysis, while roasting sorghum reduced tannin and phytic acid content. The IC50 values revealed that hibiscus (47.74 mg/mL) and rose (39.87 mg/mL) enrichment boosted antioxidant activity. Sensory evaluations favored roasted bowls across all attributes, while Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analyzer (TGA) analyses confirmed significant structural changes. The enhanced bowls exhibited greater hardness and hold hot or cold snacks for 90 min without compromising structural integrity. Additionally, these bowls demonstrated an extended shelf life, low microbial count (1×101CFU/g), reduced toxicity (3%–10% mortality in brine shrimp assays), and complete biodegradation within 15 days in wet soil. These findings indicate that sorghum-based edible bowls present a nutritious, viable, less toxic alternative to SUPs, appealing to a broad demographic, especially in the food and tourism sector, and contributing to environmental conservation by reducing plastic waste and suitable for wide consumption.